A Study of The Phenomena of Visual Pollution in Halabja and its Effects on The Psychology of Citizens - Baram, Hasim Othman; Mohammed, Osama Ashraf; Salih, Aram Omer; Omar, Daban Kadhim; Mahmood, Rawa Fayaq; Karim, Talar Mohammed (Universitas Islam Negeri Raden Intan Lampung, 2022)
Each year, new environmental threats develop. These threats can be either natural or man-made. Human-caused environmental effects are becoming more prominent and influential. Their activities and deeds endanger the ecosystem and future generations. Human, economic, and political actions are the fundamental causes of environmental pollution and damage. As a result, environmental changes have an impact on people's physical and emotional well-being. Nobody questions the fact that the environment is deteriorating. Numerous studies have demonstrated that this transition occurs and has an impact on our lives. One of the most serious concerns confronting the world today is environmental contamination. A polluted environment is one of the difficulties that everyone in society encounters. Visual pollution is a type of environmental contamination. Any human action that affects the environment is referred to as visual pollution. A lack of environmental knowledge and irresponsibility causes visual pollution. There is no doubt that pollution harms the environment's living and inanimate components because the environment is necessary for human life and other kinds of life. Any alteration in the environment will endanger the entire land ecosystem. There are various types of environmental pollution, with water, air, soil, sight, and sound pollution all the most serious..